Konsep Quadruple Helix Dalam Meningkatkan Taraf Hidup Masyarakat Melalui Pengembangan Usaha Kopi Desa Rempek Darussalam - Rulah, Kama; Pratama, Inka Nusamuda; Muningsih, Amil (Universitas Mercu Buana, 2023)
Rempek Darussalam is a village that has abundant natural resources and utilizes them well but cannot be managed well. This research was conducted with the aim of knowing the involvement and performance carried out by various stakeholders, namely government, private/business world, academics and the community, especially in improving standard of living through the development of micro, small and medium enterprises. The research method used in this research is qualitative. The results of this research show that the development of micro, small and medium enterprises in an effort to improve people's living standards has been pursued by various policy stakeholders starting from the government, private sector/business world, academics and the community, although there are still many shortcomings in the beginning. from the government and the private sector/business world which is still lacking. stiff and still less active, especially in providing training and providing capital, as well as from the academic side which is still less effective in training, mentoring, digital marketing socialization.